Pemikiran Ulama Muta’akhkhirin Berhubung Pengamalan Konsep Talfiq Dalam Penyelesaian Hukum Syarak: The Muta’akhkhirin Scholars’ Perspective on the Implementation of the Talfiq Concept in Resolving Islamic Legal Issues - Jamaludin, Mohd Hafiz; Pauzi, Norhidayah; Syed Jaafar, Syed Mohd Jeffri; Daud, Mahyudin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Talfiq is one of the methodologies to create the resolution of hukm based on the treasure of fiqh introduced by classical Islamic scholars. Despite that, the use of this methodology is still debatable and remains as mahal al-khilaf by scholars. The mut’akhkhirin scholars are most of the numerous groups that are against this concept. This contradicts the modern scholars who tend to adopt this concept to arrive at an opinion that is suitable with modern and current issues. Therefore, this article will analyse several views from the muta’akhkhirin scholars regarding the use of talfiq. This study was conducted with the qualitative method, collecting data from turath literature (classical textbooks) written by the muta’akhkhirin scholars, and it will end with analyse with the thematic methods. The result of the study found that the stick of view by the muta’akhkhirin scholars against the practice of talfiq has their own basis. The study found three main bases against the practice of talfiq; 1. The use of talfiq will lead to arriving at an opinion that is rejected by the majority of the scholars; 2. The use of the talfiq will lead to the practice of tatabbu‘ al-rukhas; and 3. The use of talfiq will lead to harm to religion.